Tool life in high speed turning with negative rake angle - Adesta, Erry Yulian Triblas; Al Hazza, Muataz Hazza Faizi (Trans Tech Publications, Switzerland, 2011)
The present work studies some aspects of turning process applied on mild steel using cermets tools at high speed cutting (1000mm/min) by using negative rake angle (90 to 12). The influence of increasing the cutting speed and negative rake angle on flank tool wear, cutting force, feeding forces and tool temperature were analyzed. The research studies and concentrates on the tool life estimation and the effect of the negative rake angle and higher cutting speed on tool life. It was found that the maximum tool life is obtained in (-6) rake angle for the different cutting parameters.